INNOVATIVE APPROACH TO STUDENT EDUCATION ON THE BASE OF PIERLS' TASKS (Multidisciplinary Journal of Science and Technology, 2024)
In this article, a new approach to the education of the young generation, which is a global problem in the age of information technologies, is discussed, the importance of PIRLS in this process and the methodology of its use are discussed